Which of the following demonstrates the Commutative Property of Multiplication?

2(6a − 3) = (6a − 3) ⋅ 2
2(6a − 3) = 12a − 6
12a − 6 = (6a − 3) ⋅ 2
(2 ⋅ 6a) − 3 = 2(6a − 3)

Respuesta :

Answer:

2(6a − 3) = (6a − 3) ⋅ 2

Step-by-step explanation:

here it is

Commutative means 'you can swap them'. I.e., a+b = b+a, addition is commutative. Subtraction is not.

The first answer: 2(6a − 3) = (6a − 3) ⋅ 2  is an example where 2 and (6a-3) are the factors that can be swapped, because multiplication is commutative.

ACCESS MORE